PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUASAN KONSUMEN (Studi Pada PT. Indojaya Agrinusa Unit Hatchery Pekanbaru) - Ajannah, Anita; Harianto, Meyzi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted at PT. Indojaya Agrinusa Pekanbaru Hatchery Unit as for the purpose of this study is to determine the effect of quality and price product on consumer satisfaction (Study at PT. Indojaya Agrinusa Pekanbaru Hatchery Unit). The quality and price Products are independent variables (X1X2) While consumer satisfaction is the dependent variable (Y). The method in this study is quantitative where the sample used in this study is consumers of PT. Indojaya Agrinusa Pekanbaru Hatchery Unit was taken as many as 100 respondents. The data obtained from the results of baking and then processed to be tested with statistics through the SPSS program. From the results of testing conducted shows that quality product partially affects consumer satisfaction, prices partially affect consumer satisfaction, and quality and prices product have a positive and significant effect on customer satisfaction (study at PT. Indojaya Agrinusa Pekanbaru Hatchery Unit). Keywords: Product  Quality, Price and Satisfaction Consumer